The puzzle of interpersonal trust (2014)
One aspect not sufficiently considered in solving the social dilemma of redistribution of wealth is the mediating role of trust. In this article, I present preliminary evidence in this regard. Later, I consider several mechanisms that may explain the observed levels of interpersonal trust in 54 countries included in the fifth World Values ​​Survey (2005-2008). The results of a multivariate statistical model indicate that the best performing variables are the level of wealth, political stability, with a negative effect , participation and inclusion in decision -making processes . However, an analysis of the levels of interpersonal trust based on surveys conducted between 1996 and Latinobarometer 2010 shows partly different results. Later models could resolve this disparity considering the variety of historical trajectories in each region or modeling the effect of mechanisms from social, economic and political structure differently.